Islamic Education Learning Approaches in Shaping Students’ Emotional Intelligence in the Digital Age - Firman Mansir; Abdul Karim (Hayula: Jurnal Indonesia Studi Islam Multi-disiplin, 2020)
Over the last several decades have witnessed nothing short of a transformation in the study of religion. The human race lives in a time of deep concern for the future of the biosphere. Globalization can bring a paradox to the practice of Islamic education. Islamic education has a significant role in shaping the ethics and morals in the life of the people and of the nation to create religious and devoted people. The objective of this study was to describe the Islamic education learning approaches discourse strategy, the basic concept, classification, strategies, and its steps of developingto develop. This is a qualitative study using the main data source from literature, so it needs data elaboration from various literature. The data collection procedure by analyzing the literature using an analytical descriptive method. The results show that it’s time for Islamic education learning to develop an active learning method through good strategic planning so it can shape the students’ emotional intelligence. The implication of this result is scientific contribution and the concept of strategic approaches to Islamic education and as one of the efforts in developing the students’ emotional intelligence.